Предмет: Алгебра,
автор: muratdaulet08
Решите уравнение:
(x² - 6)(x² + 2) = (x² - 2)² - x
IUV:
автор вопроса - спамит в чужих вопросах
Ответы
Автор ответа:
1
Ответ:
(x^2-6)(x^2+2)=(x^2-2)^2-x
x^4+2x^2-6x^2-12=x^4-4x^2+4-x
2x^2-6x^2-12=-4x^2+4-x
-4x^2-12=-4x^2+4-x
-12=4-x
x=4+12
x=16
Автор ответа:
0
Объяснение:
(х^2-6)(х^2+2)=(х^2-2)^2-х
х^4+2х^2-6х^2-12=х^4-4х^2+4-х
Х^4+2х^2-6х^2-х^4+4х^2+х=12+4
Х=16
Похожие вопросы
Предмет: Русский язык,
автор: Kairat02
Предмет: Русский язык,
автор: burantsev05
Предмет: Русский язык,
автор: ksusha200342
Предмет: Математика,
автор: фомка5
Предмет: Геометрия,
автор: inst0asoyan76